IMPLEMENTASI KEBIJAKAN PELIMPAHAN WEWENANG KEPADA KECAMATAN DALAM PEMUNGUTAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN DI LUAR KAWASAN DI KABUPATEN TANGERANG PROVINSI BANTEN - Ira Meiyenti; Abdi Praja Ari Putera (Institut Pemerintahan Dalam Negeri, 2017)
The Regional Government of Tangerang Regency delegates the authority to collect retribution in the sub-district sector regulated in Tangerang Regent’s Regulation No. 14 of 2014 on the Delegation of some of the Regent’s Authority to the Camat to Implement Regional Government Affairs. However, in the implementation has not received response and intensive attention from the community or the licensing service providers either the district or Integrated Licensing Service Board. On the background of the problem, the researcher conducted a study focusing on “IMPLEMENTATION OF POLICY AUTHORITY POLICY TO SUPPLY IN CONSTRUCTION RETRIBUTION PERMITS PERMITS BUILDING OUTSIDE THE REGION IN TANGERANG REGENCY”. In this research the writer use descriptive research method with inductive approach. Data obtained from primary data sources and secondary data, obtained through interviews with related parties, combined with observation and documentation. The result of this research concludes that the implementation of the Abstract of Authority of Levy of License to Establish Building Outside the Area in Kelapadua Subdistrict has not run optimally yet. In addition, the monitoring/ monitoring conducted by Kelapadua District implementers on mandatory retribution is considered less than optimal, the officers who should conduct surveys to the field for two times during the process of making most can only be done 1 times even there are people who in the process of service has been 2 months But has not yet obtained a building permit letter Based on the observations, the authors suggest that the addition of field officer field personnel, controlling the compulsory retribution, the policy of Tangerang regency government should be consistent in improving the maid in the program Delegation of Authorization Levy Levy Permit Building Outside the Area, Availability of structured communication network, and conduct socialization And carry out the process of identifying the development as a whole, as well as providing warning (preventive) and sanction (repressive) to people who deliberately avoid making or pay retribution in order to have a deterrent effect that can stimulate local revenue. Keywords: policy implementation, authority delegation, district